2023
DOI: 10.3389/fimmu.2023.1206299
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal γδ T cells: functions in the gut and in the distant organs

Abstract: Located in the frontline against the largest population of microbiota, the intestinal mucosa of mammals has evolved to become an effective immune system. γδ T cells, a unique T cell subpopulation, are rare in circulation blood and lymphoid tissues, but rich in the intestinal mucosa, particularly in the epithelium. Via rapid production of cytokines and growth factors, intestinal γδ T cells are key contributors to epithelial homeostasis and immune surveillance of infection. Intriguingly, recent studies have reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Molecules such as IL-7, IL-15, butyrophilin-like molecules (BTNL), the ligand-activated transcription factor AhR (aryl hydrocarbon receptor), and aldo-keto reductase 1B8 (AKR1B8) are essential for the proliferation, survival, and maintenance of the homeostatic mechanism of intestinal γδ T cells [48]. The G protein-coupled receptor GPR18 can also regulate the expansion of γδ T cells in the gut and their positioning next to epithelial cells [49,50].…”
Section: Intestinal γδ T Cellsmentioning
confidence: 99%
“…Molecules such as IL-7, IL-15, butyrophilin-like molecules (BTNL), the ligand-activated transcription factor AhR (aryl hydrocarbon receptor), and aldo-keto reductase 1B8 (AKR1B8) are essential for the proliferation, survival, and maintenance of the homeostatic mechanism of intestinal γδ T cells [48]. The G protein-coupled receptor GPR18 can also regulate the expansion of γδ T cells in the gut and their positioning next to epithelial cells [49,50].…”
Section: Intestinal γδ T Cellsmentioning
confidence: 99%
“…They are encoded by a lower number of V, D and J segments with a limited clonotypic diversity [ 41 ]. Functionally, gamma-delta T cells rapidly respond to microbial antigens, with the production of IFN-gamma, TNF-alpha and IL-17 [ 42 ]. It has been reported that gamma-delta T cells from long-lived memory cells, following bacterial challenge, can permanently reside in the affected tissue.…”
Section: T Cell Receptor and T Cell Activationmentioning
confidence: 99%
“…It has been hypothesized that CD8+TCRγδ + may play a role in the preservation of intestinal homeostasis by regulating the mucosal immune response and/or by contributing to the epithelial cell layer maintenance. Functional properties of TCRγδ+ IELs can be mediated by NK receptors (such as NKGD) expressed on a fraction of these cells [75]. At the same time, CD8+ TCRαβ+ IELs have been suggested to kill intestinal epithelial cells (IECs) in an NKG2D-MICA-dependent manner during CeD [76].…”
Section: Cd8 T Lymphocytes With Regulatory Activitymentioning
confidence: 99%